The effects of plasticity-based cognitive rehabilitation on resting-state functional connectivity in chronic traumatic brain injury: A pilot study. - Lindsey, Hannah M.; Lazar, Mariana; Mercuri, Giulia; Rath, Joseph F.; Bushnik, Tamara; Flanagan, Steven; Voelbel, Gerald T. (NeuroRehabilitation, 2022)
BACKGROUND: Traumatic brain injury (TBI) often results in chronic impairments to cognitive function, and these may be related to disrupted functional connectivity (FC) of the brain at rest. OBJECTIVE: To investigate changes in default mode network (DMN) FC in adults with chronic TBI following 40 hours of auditory processing speed training. METHODS: Eleven adults with chronic TBI underwent 40-hours of auditory processing speed training over 13-weeks and seven adults with chronic TBI were assigned to a non-intervention control group. For all participants, resting-state FC and cognitive and self-reported function were measured at baseline and at a follow-up visit 13-weeks later. RESULTS: No significant group differences in cognitive function or resting-state FC were observed at baseline. Following training, the intervention group demonstrated objective and subjective improvements on cognitive measures with moderate-to-large effect sizes. Repeated measures ANCOVAs revealed significant (p < 0.001) group×time interactions, suggesting training-related changes in DMN FC, and semipartial correlations demonstrated that these were associated with changes in cognitive functioning. CONCLUSIONS: Changes in the FC between the DMN and other resting-state networks involved in the maintenance and manipulation of internal information, attention, and sensorimotor functioning may be facilitated through consistent participation in plasticity-based auditory processing speed training in adults with chronic TBI.